Dinamika Firm Value di Sektor Infrastruktur Bei: Integrasi Indikator Growth, Leverage, Liquidity, dan Firm Size - Sisca Contesa (Journal of Economics and Business UBS, 2026)
The primary objective of a company is to enhance its value as a means of maximizing shareholder wealth. This can be achieved through strong financial performance, including improvements in sales growth, debt-to-equity ratio, firm size, and liquidity (current ratio), which collectively play a role in attracting investors and strengthening market confidence. This research is intended to analyze the influence of sales growth, debt-to-equity ratio (DER), firm size, and current ratio on firm value in companies operating within the infrastructure sector listed on the Indonesia Stock Exchange (IDX). An associative research design with a quantitative approach was adopted in this study. The population consisted of 64 companies, from which 32 firms were selected as samples using purposive sampling techniques. The data were processed and analyzed using Statistical Product and Service Solutions (SPSS) version 25. The findings reveal that sales growth, DER, and firm size do not exhibit a statistically significant impact on firm value. However, the current ratio demonstrates a positive and significant influence on firm value among infrastructure companies listed on the IDX. In summary, the study concludes that sales growth, debt-to-equity ratio, and firm size are not determinants of firm value, whereas the current ratio plays a significant positive role in influencing firm value in infrastructure sector companies listed on the Indonesia Stock Exchange